2018
DOI: 10.5194/tc-12-3017-2018
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-derived sea ice export and its impact on Arctic ice mass balance

Abstract: Abstract. Sea ice volume export through the Fram Strait represents an important freshwater input to the North Atlantic, which could in turn modulate the intensity of the thermohaline circulation. It also contributes significantly to variations in Arctic ice mass balance. We present the first estimates of winter sea ice volume export through the Fram Strait using CryoSat-2 sea ice thickness retrievals and three different ice drift products for the years 2010 to 2017. The monthly export varies between −21 and −5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 41 publications
9
99
0
Order By: Relevance
“…Although the thermodynamic ice melting processes have greatly contributed to the changes in Arctic sea ice, dynamic ice export out of the Arctic Ocean has also been identified as a key contributing factor (Kwok 2009;Smedsrud et al 2011;Langehaug et al 2013), in particular for multiyear ice loss (Ricker et al 2018). According to previous studies, the southward sea ice export across Fram Strait (the location is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the thermodynamic ice melting processes have greatly contributed to the changes in Arctic sea ice, dynamic ice export out of the Arctic Ocean has also been identified as a key contributing factor (Kwok 2009;Smedsrud et al 2011;Langehaug et al 2013), in particular for multiyear ice loss (Ricker et al 2018). According to previous studies, the southward sea ice export across Fram Strait (the location is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the southward sea ice export across Fram Strait (the location is shown in Fig. 1) into the Greenland-Iceland-Norwegian (GIN) Sea (or Nordic Seas), which amounts to 2000-3000 km 3 per year Spreen et al 2009), comprises the largest portion of the total Arctic sea ice export (e.g., Carmack et al 2016;Ricker et al 2018). Part of this considerable amount of freshwater has been found flowing along the East Greenland Current into the Nordic Seas, which is closely related to the freshening of Greenland and Labrador Sea (Dickson et al 1988;Holland et al 2006;Koenigk et al 2006), and thus has huge impact on the global ocean circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The sea ice volume flux through the Fram Strait was calculated as a product of monthly average sea ice thickness, area of the grid cell and the sea ice drift velocity (Ricker et al, 2018). Note, that the PIOMAS sea ice thickness represents the mean (Fig.…”
Section: Fram Strait and Denmark Strait Sea Ice Volume Flux From Piomasmentioning
confidence: 99%
“…The total ice volume flux through the Fram Strait was derived for the period from 1979 to 2017 for each months. A similar methodology was used to assess the sea ice volume flux though the Denmark strait along the meridional section (66 • N and Ricker et al (2018). The gate and the methodology used here was adopted from Ricker et al (2018), while in other two studies somewhat different methodologies and gates locations ( Fig.…”
Section: Fram Strait and Denmark Strait Sea Ice Volume Flux From Piomasmentioning
confidence: 99%
“…Additional limitations arise from current remote sensing capabilities for studying the complex dynamics at such gates and a mis-match in the spatial resolution of the applied data sources (e.g. Ricker et al 2018). Given the large across-strait variability in seaice type, thickness and motion, SAR-based estimates of the sea-ice motion are possibly the best way to proceed (Smedsrud et al 2017) provided enough in situ data, e.g.…”
Section: Sea Ice Thickness Uncertaintymentioning
confidence: 99%